Contact vs. Information: What shapes attitudes towards immigration? Evidence from an experiment in schools - Erminia Florio (Global Labor Organization (GLO), 2020)
We analyze whether (correct) information provision on immigration is more effective than contact in shaping attitudes towards immigration. We collect data from a randomized experiment in 18 middle- and high-school classes in the city of Rome. Half of the classes meet a refugee from Mauritania, whereas the rest of them attend a lecture on figures and numbers on immigration in Italy and the world. On average, students develop better attitudes towards immigration (especially in the case of policy preferences and the perceived number of immigrants in their country) after the information treatment more than they do after the contact treatment, whereas neither treatment affects feelings associated to immigrants. Also, students having received the information treatment strongly adjust their knowledge on immigration. However, students' individual characteristics and school type (i.e. middle vs. high school) affect treatments' effectiveness.
Keywords: C93; J15; Z1; Z13; 330; Attitudes towards immigration; Information Provision; Contact Theory; Randomized Experiment